Pengaruh Penggunaan Model Pembelajaran Contextual Teaching And Learning Terhadap Hasil Belajar Bahasa Indonesia Siswa Kelas V Sekolah Dasar - Steven Mandey (Peneliti.net, 2022)
This study aims to determine and analyze the effect of the Contextual Teaching and Learning learning model on Indonesian language learning achievement for Class V at Hati Kudus Sonder Catholic Elementary School. Research in this study is a quantitative approach. This method is called the quantitative method because the research data is in the form of numbers and the analysis uses statistics. The conclusions obtained from this study indicate that the average learning outcomes between students who are taught using the Contextual Teaching and Learning learning model are compared to learning outcomes before using the Contextual Teaching and Learning learning model in Indonesian language subjects in class V at Hati Kudus Sonder Catholic Elementary School. This is indicated by the average pretest score which only reached 37.22. In the use of the Contextual Teaching and Learning learning model, the average student learning outcomes in the post-test reached 84.72, which means that it exceeds the Minimum Completeness Criteria standard both individually and classically which is determined to be 75. From this data, it shows that the average difference in the increase in the result score pre-test and post-test in the research class has difference of 47.50.